ANTIBACTERIAL ACTIVITY OF BAWANG DAYAK (ELEUTHERINE SP.) AND TAWAS UT (AMPELOCISSUS SP.) FROM CENTRAL KALIMANTAN AGAINST PROPIONIBACTERIUM ACNES - ARDHANY, SYAHRIDA DIAN (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of the present study was to investigate phytochemical screenings and the in vitro effect antibacterial of BD (Eleutherine Sp.) and TU (Ampelocissus Sp.) against Propionibacterium acnes. Methods: The antibacterial activity was investigated against Propionibacterium acnes by well diffusion method. Results: Preliminary phytochemical screenings of BD ethanolic extract were found positive alkaloid, saponin, tannins, and steroid while TU positive flavonoid, saponin, tannins, steroid, and triterpenoid. Antibacterial activity against Propionibacterium acnes of ethanolic extract BD with concentration 25 mg/ml and 50 mg/ml showed the zone of inhibition 3.23 mm and 7.8 mm with category weak activity while ethanolic extract TU with same concentration showed zone of inhibition 10 mm (weak activity) and 16.3 mm (moderate activity) which mean ethanolic extract TU have better antibacterial activity. A combination ethanolic extract of both with variant ratio showed a zone of inhibition 6.7 mm (1:1), 3.9 mm (1:2), and 3.63 mm (2:1). Conclusion: In this present study showed the highest potential antibacterial activity against propionibacterium acnes is an ethanolic extract of TU and The best ratio combination is 1:1. Furthermore, this study needs more research with variant concentration so that may be possible to be used as natural anti-acne formulations.